Drug-microenvironment perturbations reveal resistance mechanisms and prognostic subgroups in CLL - Bruch, Peter-Martin; Giles, Holly AR; Kolb, Carolin; Herbst, Sophie; Becirovic, Tina; Roider, Tobias; Lu, Junyan; Scheinost, Sebastian; Wagner, Lena; Huellein, Jennifer; Berest, Ivan; Kriegsmann, Mark; et al. (Molecular systems biology, 2022)
Abstract The tumour microenvironment and genetic alterations collectively influence drug efficacy in cancer, but current evidence is limited and systematic analyses are lacking. Using chronic lymphocytic leukaemia (CLL) as a model disease, we investigated the influence of 17 microenvironmental stimuli on 12 drugs in 192 genetically characterised patient samples. Based on microenvironmental response, we identified four subgroups with distinct clinical outcomes beyond known prognostic markers. Response to multiple microenvironmental stimuli was amplified in trisomy 12 samples. Trisomy 12 was associated with a distinct epigenetic signature. Bromodomain inhibition reversed this epigenetic profile and could be used to target microenvironmental signalling in trisomy 12 CLL. We quantified the impact of microenvironmental stimuli on drug response and their dependence on genetic alterations, identifying interleukin 4 (IL4) and Toll-like receptor (TLR) stimulation as the strongest actuators of drug resistance. IL4 and TLR signalling activity was increased in CLL-infiltrated lymph nodes compared with healthy samples. High IL4 activity correlated with faster disease progression. The publicly available dataset can facilitate the investigation of cell-extrinsic mechanisms of drug resistance and disease progression.
Gesehen am 20.03.2023